Terapi Fobia Spesifik dengan Metode Akupunktur Somatosensorik - Dharma Kumara Widya; Willie Japaries; Lismin Dirwanto; Frisca Desma (Jurnal Kesehatan, 2021)
Background: Phobia or morbid fear sensation is among the most common psychiatric problems in the community. The existing methods to treat it mostly are time consuming and carrying adverse effects. Methods: This report describes a simple method of acupuncture therapy could immediately overcome specific phobia in two patients. Case descriptions: Two patients suffering specific phobia towards gecko and snake, respectively. They were asked to imagine the object of phobia, so as to incur the phobic emotional and bodily sensations. Acupuncture was done upon the body area suffering the bodily sensation of phobia, until the sensation was replaced by needling sensation (de qi). With the vanish of the phobic bodily sensation, the emotional phobic reaction vanished too. Conclusion: The somatosensory acupuncture therapy is simple, safe and effective in alleviating specific phobia in one treatment session. It is explorable further as a quick fix for specific phobia.